The Effect of Brand Image of Food and Beverage Products by People with Disabilities on Sales Volume of KUBE “BISA” PERPENCA - Asrorul Mais; David Kristian Susilo; Hanif Hadinata Utama (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to determine the effect of brand image on sales volume in KUBE “BISA” PERPENCA joint business group where most of its members have disabilities, whether the level of product sales can increase by using a brand image strategy. In this study, researchers used a qualitative descriptive method, where researchers collected, reviewed, and described the results of the field research to determine the effect of brand image on KUBE "BISA" formed by PERPENCA. This research was conducted in August 2022 with a period of approximately one month. This study has two types of data groups, the main data and supporting data. The main data of this research is data sourced from KUBE (join business group) which uses brand image on its products. Supporting data in this study is data sourced from all members of KUBE "BISA" PERPENCA who use brand image. The data of this study were collected from unstructured observations, interviews or brief interviews about the influence before and after using brand image, as well as documenting data from all events occurring in the field. After performing the brand image, most members of the “BISA” joint business group admitted that there are increases in sales volume. This was also felt by other members who initially stated that their products were selling well, but after making brand image and changing to more attractive packaging, more customers are now interested on their products, for example, the sales of opak gulung (egg rolls) of Karang Anom saw an increase from 33% to 60% due to the brand imaging of such products.